Kualitas Pelayanan Badan Penyelenggaraan Jaminan Sosial (BPJS) Ketenagakerjaan Kota Padang - Sari, Gustia; Putri, Sinta Westika (Al-DYAS, 2026)
Public service quality is a crucial aspect in building public trust and satisfaction, including in the administration of employment social security by BPJS Ketenagakerjaan Padang City, which is required to provide high-quality, effective, and responsive services to participants’ needs. This study aimed to analyze the service quality of BPJS Ketenagakerjaan Padang City based on service quality dimensions and to identify the factors that influence this quality. A qualitative approach was employed, with data collected through interviews, observations, and documentation, and subsequently analyzed using NVivo 15 software through Hierarchy Chart and Project Map visualizations within a descriptive analytical framework. The findings show that the service quality of BPJS Ketenagakerjaan Padang City has met most of Zeithaml’s service quality principles, covering the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. However, service quality has not yet been fully optimal, as constraints are still encountered in the form of system disruptions, delays in claim processing, document discrepancies, participants’ lack of understanding of regulations, and uneven speed of service and empathetic attitudes among officers. The study also finds that Moenir’s five key factors—awareness, regulations, organization, officers’ abilities and skills, and service facilities—make significant contributions both as supporting and inhibiting elements in service delivery. These findings underscore that BPJS Ketenagakerjaan’s service quality plays an important role in enhancing participants’ satisfaction and perceptions, while also indicating that the assurance and empathy dimensions still require strengthening so that services become more adaptive and better able to meet participants’ expectations.